Incidental Melanocytic Nevi in Hemorrhoidectomy Specimens. (April 2016) - Val-Bernal, J. Fernando; Mayorga, Marta; Val, Daniel
Abstract : Background: Benign melanocytic nevi (MN) of the anal canal are exceptional and require adequate differential diagnosis. There are no data on incidence of these lesions. Only a single case report of hemorrhoid with an MN has been reported. The necessity of routine pathologic evaluation of hemorrhoidectomy specimens has been questioned. Material and Methods: The authors undertook a retrospective histologic study of the hemorrhoidal tissue obtained in a series of 1918 consecutive hemorrhoidectomies performed between January 2004 and November 2012. Results: Incidental hemorrhoidal MN were detected in 4 (0.21%) patients. The ratio observed was 1 nevus in 480 specimens. Lesions were intradermal or purely junctional in nature. There were no mitoses or architectural disorder. An intradermal nevus showed localized pagetoid melanocytes. The mean age of the patients was 56.5 years (range 47–73 years). The mean size of nevi was 5.86 mm (range 1.89–13.86 mm). All cases were present in external hemorrhoids. Conclusions: Although uncommonly, incidental MN can be observed in hemorrhoidal tissue. They may show features of flexural nevi and pagetoid melanocytes. Routine histopathological study of hemorrhoidectomy specimens would help to detect benign or malignant melanocytic tumors of the anal canal as these neoplasms can be easily missed clinically. Furthermore, this practice would allow early diagnosis of significant associated processes.